THE AGILE MARKETING PLAYBOOK: MANAGING STRATEGY IN A REAL-TIME WORLD - Heni Esra Simanjuntak; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This article examines the growing role of agile marketing in managing strategy within a real-time, dynamic environment shaped by rapid digital transformation and evolving consumer behavior. Traditional marketing approaches, characterized by long planning cycles and limited flexibility, are increasingly insufficient in responding to fast-changing market conditions. Using a narrative literature review, this study synthesizes insights from academic and practitioner sources to explore key concepts, frameworks, and challenges associated with agile marketing. The findings highlight four core themes: agility as a strategic capability, continuous experimentation, customer-centricity, and data-driven decision-making. Based on these insights, the study proposes an Agile Marketing Playbook consisting of four components: strategic alignment, execution cycles, technology enablement, and team structure. This framework provides a structured approach for integrating agile principles into marketing strategy while maintaining alignment with broader organizational goals. The study contributes theoretically by extending agile concepts to the strategic level and offers practical guidance for organizations navigating real-time marketing complexities. However, its narrative approach limits comprehensiveness, suggesting the need for future empirical validation across contexts.